Pyrrolopyrrole aza-BODIPY near-infrared photosensitizer for dual-mode imaging-guided photothermal cancer therapy. Issue 6 (20th December 2018) - Wu, Chaolong; Huang, Xiaoyu; Tang, Yunyun; Xiao, Wanyue; Sun, Liguo; Shao, Jinjun; Dong, Xiaochen
Abstract : A NIR photosensitizer pyrrolopyrrole aza-BODIPY (PPAB ) was synthesized in a straightforward manner. Abstract : A NIR photosensitizer pyrrolopyrrole aza-BODIPY (PPAB ) was synthesized in a straightforward manner. Through the use ofPPAB NPs as a photothermal agent, photoacoustic imaging (PAI) and NIR fluorescence imaging (NIR-FI) can be achieved in vivo . In addition, the photothermal ablation of tumor cells can be realized both in vitro and in vivo, even at a low concentration (0.5 mg kg −1 ).